The politics of participation in post-disaster planning: local needs and perspectives versus global aspirations in plans for Montserrat's new capital. Issue 6 (1st November 2020) - Hooper, Michael
Abstract : Drawing on interviews with residents and officials, this article investigates how local needs and perceptions have been balanced against other aspirations in plans for Montserrat's new capital. This new settlement would replace the former capital, Plymouth, which was destroyed in a volcanic eruption and abandoned permanently in 1997. The article finds that residents' needs and perspectives were given relatively little attention in the planning process and resulting plans for the capital. However, it also finds that residents and officials now hold relatively similar views on the existing plans and on what attributes are ultimately desirable in a capital. This suggests that adopting more participatory planning approaches in the future could build on this shared vision and result in plans that are more publicly and politically sustainable and more likely to be realised.